Mesothelioma - Maciá, Sonia (IntechOpen, 2020)
Mesothelioma is an aggressive cancer with very poor survival and lack of treatment options. This book, written by a diverse panel of experts, presents a description of the most relevant topics on epidemiology, diagnosis, biomarkers, and treatment updates, including interesting discussion on molecular mechanisms, prognostic features, and novel therapies that are either approved or under clinical development for this challenging disease. It also discusses and explains genetic biomarkers, as there may be a role for some nuclear regulatory genes and proteins in development of mesothelioma, although targeted therapies so far have had limited impact.